Primary Results on the investigation of lectin from some botanical families in Vinh Phuc, Phu Tho and Yen Bai provinces - Chau, Truong Van (Academia Journal of Biology, 2015)
The investigated results from 37 plant species in Vinh Phuc, Phu Tho and Yen Bai provinces have showed that 50% of investigated species contained lectin and mainly concentrated in species of Moraceae and Fabaceae. Investigated species of Solanaceae, Cucurbitaceae, Amaranthaceae and Rutaceae did not contain lectin.